Ductal Adenocarcinoma of the Prostate: A Case Report - Hayashi, Yutaro (Case Rep Oncol, 2016)
Ductal adenocarcinoma is an unusual variant of adenocarcinoma of the prostate. A 73-year-old male was referred to our hospital for the further examination of an elevated prostate-specific antigen level of 23.4 ng/mL. Radical prostatectomy (RP) was performed based on the diagnosis obtained by a prostate needle biopsy. The RP specimen revealed ductal adenocarcinoma of the prostate with positive capsular penetration. We herein report a rare case of ductal adenocarcinoma of the prostate.